Tool development for single-mRNA translation dynamics imaging and quantification - Galindo, Gabriel, author; Stasevich, Timothy, advisor; Ross, Eric, committee member; Di Pietro, Santiago, committee member; Geiss, Brian, committee member (Colorado State University. Libraries, 2026)
Translation is an essential process conserved across all forms of life, serving as the final step in converting genetic information into the functional protein products that sustain cellular life. The precise regulation of translation, controlling what is made, when, and in what quantity, is critical for cellular homeostasis, and its disruption underlies a wide range of diseases, such as cancer and neurodegeneration. Though powerful tools have been developed to study translation, including polysome profiling, ribosome profiling, and fixed-cell imaging, these approaches rely on population-level measurements and therefore capture only static snapshots of the process, obscuring the heterogeneity and temporal dynamics of translation. To address these limitations, Nascent Chain Tracking (NCT) was developed, enabling the real-time visualization of translation on individual mRNA molecules in living cells. NCT uses arrays of epitope repeats at the N-terminus of a reporter protein that are co-translationally bound by fluorescently labeled intrabodies as they emerge from the ribosome, generating a bright signal at active translation sites. Combined with mRNA labeling systems such as MS2-MCP, NCT enables the simultaneous tracking of individual mRNAs and their translational activity with single-molecule resolution. Since its development, NCT has illuminated a broad range of translational phenomena including frameshifting, IRES-mediated initiation, and Argonaute-mediated repression. Despite this growing list of applications, NCT remains technically demanding. The need to balance multiple imaging components, limitations imposed by photobleaching during long-term imaging, and inconsistencies in how translation kinetics are measured across the field have collectively limited its widespread adoption. This dissertation presents three advances that address these challenges and expand the capabilities of NCT. To simplify experimental setup, we develop All Probes Plasmids (APPs), single-plasmid systems that encode all necessary NCT imaging probes at optimized expression levels using internal ribosomal entry and skip sequences. APPs reduce the optimization burden associated with multi-component probe expression, lower background signal, and enable flexible multicolor imaging. To expand the intrabody toolkit available for NCT and beyond, we develop an AI-driven pipeline for converting existing antibody sequences into functional intrabodies. Using AlphaFold2, ProteinMPNN, and live-cell screening, we generate a panel of intrabodies targeting synthetic and viral epitopes, and diverse histone modifications. This work establishes a generalizable and scalable framework for intrabody development, enabling the dynamic imaging of epigenetic marks in living cells. Finally, to address longstanding discrepancies in reported ribosome elongation rates, we cross-validate three independent NCT-based measurement approaches: harringtonine runoff assays, fluorescence recovery after photobleaching, and fluorescence correlation spectroscopy (FCS). We identify an immobile ribosome fraction as a source of systematic underestimation in standard harringtonine analysis and develop a corrected pipeline that reconciles all three methods with ribosome profiling data. With single-mRNA FCS, we uncover heterogeneity in elongation rates within the mRNA population. We further demonstrate that FCS can quantify ribosome stalling at defined sequences that harringtonine fails to resolve, establishing FCS as a particularly sensitive tool for characterizing translation. Together, these contributions establish an expanded methodological foundation for single-molecule translation imaging, advancing our ability to study translational regulation with greater precision and accessibility in living cells.